Partisan Cities: How State‐Local Political Alignment Shapes Credit Risk and Information Processing in the Municipal Bond Market - DAGOSTINO, RAMONA; NAKHMURINA, ANYA (Journal of Accounting Research, 2026)
ABSTRACT This paper studies how partisan alignment between city leaders and state governors shapes information processing and bond pricing in the municipal bond market. Using a novel data set on 1,045 U.S. cities from 2005 to 2019, we show that cities with the same political affiliation as the state governor face 9 basis points lower borrowing costs than misaligned cities. The effect is stronger for riskier bonds, in states where governors hold greater authority, and for fiscally dependent cities. Aligned cities also receive more aid during fiscal distress. Partisan alignment shapes how investors interpret and respond to financial information: Nondisclosure and adverse audit findings raise borrowing costs primarily for misaligned cities, while penalties for aligned cities are markedly smaller.